Acitretin-Induced systemic capillary leak syndrome - Kolluri Siva Bala Vaishnavi; Geeta Kiran Arakkal; M Lohita; Sandeep Kodali (Wolters Kluwer Medknow Publications, 2023)
Systemic capillary leak syndrome (SCLS) is a potentially life-threatening condition characterized by recurrent episodes of massive plasma sequestration into the interstitial space causing vascular collapse. SCLS is a rare syndrome where only a few cases are published in literature. The etiology being either idiopathic (Clarkson's disease) or secondary to underlying causes such as sepsis and drugs and diagnosis is often missed due to nonspecific presentation. We hereby present a case of pustular psoriasis on acitretin who developed SCLS after increasing the dose and eventually succumbed. Acitretin is considered the drug of choice in extensive psoriasis despite having side effect profiles. Although most of them are dose dependent and not life threatening. This is one of the rare complications where early detection of the condition, withdrawal of the drug, and appropriate management can be lifesaving.